2020
DOI: 10.1051/0004-6361/202038146
|View full text |Cite
|
Sign up to set email alerts
|

ALMA Deep Field in SSA22

Abstract: Deep surveys with the Atacama Large Millimeter Array (ALMA) have uncovered a population of dusty star-forming galaxies which are faint or even undetected at optical to near-infrared wavelengths. Their faintness at short wavelengths makes the detailed characterization of the population challenging. Here we present a spectroscopic redshift identification and a characterization of one of these near-infrared-dark galaxies discovered by an ALMA deep survey. The detection of [C I](1–0) and CO(4–3) emission lines det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 65 publications
6
48
0
Order By: Relevance
“…Franco et al (2018) discussed four ALMA-detected sources in the GOODS-S region which lacked 160 -detections, two of which are in the earlier Simpson et al (2014) study (see also Zhou et al 2020). Yamaguchi et al (2019) found two examples in similar ALMA observations of the same region (one previously identified by Cowie et al 2018), while Umehata et al (2020) obtained a spectroscopic redshift of = 3.99 for a near-infrared-faint source uncovered in an ALMA survey in the SSA 22 region. There have also been examples studied through the selection of sources with very red Herschel SPIRE colours (e.g.…”
Section: Introductionsupporting
confidence: 62%
“…Franco et al (2018) discussed four ALMA-detected sources in the GOODS-S region which lacked 160 -detections, two of which are in the earlier Simpson et al (2014) study (see also Zhou et al 2020). Yamaguchi et al (2019) found two examples in similar ALMA observations of the same region (one previously identified by Cowie et al 2018), while Umehata et al (2020) obtained a spectroscopic redshift of = 3.99 for a near-infrared-faint source uncovered in an ALMA survey in the SSA 22 region. There have also been examples studied through the selection of sources with very red Herschel SPIRE colours (e.g.…”
Section: Introductionsupporting
confidence: 62%
“…The confirmed [C II] emitters are near-infrared blank or faint SMGs (K s >24 ABmag). AS2COS0034.1/34.2 do not have any clear optical/ near-infrared counterparts, which is consistent with them lying at z4 (e.g., Simpson et al 2014;Wang et al 2019;Dudzevičiūtė et al 2020;Umehata et al 2020;Smail et al 2020). We use the S 870μm /S 3GHz flux ratio as a crude redshift indicator (e.g., Carilli & Yun 1999;Barger et al 2000;Smail et al 2000).…”
Section: Line Identificationsupporting
confidence: 56%
“…The spread at the UV/optical wavelengths seen in Fig. 1(b) highlights the variety of the SEDs of the 450-μm sources, ranging from unobscured (A V ∼ 0) Lyman-break galaxies, through more typical A V ∼ 1 star-forming galaxies similar to those selected using the BzK criteria (Daddi et al 2004), to higher-A V systems such as Extremely Red Objects (Smail et al 2004) and the near-infrared faint populations (Simpson et al 2014;Franco et al 2018;Smail et al 2020;Umehata et al 2020).…”
Section: Optical/near-infrared Propertiesmentioning
confidence: 93%